2020
DOI: 10.3847/2041-8213/ab919e
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated Mg-rich Amorphous Silicates: A New Component of the 3.2 μm Absorption Band of Comet 67P/Churyumov–Gerasimenko

Abstract: The VIRTIS imaging spectrometer aboard Rosetta has shown that the nucleus surface of comet 67P/Churyumov-Gerasimenko (67P/CG) is characterized by a broad absorption band at around 3.2 µm. The feature is ubiquitous across the surface and its attribution to (a) specific material(s) has been challenging. In the present paper, we report an experimental investigation showing that the interaction of hydrogen atoms with Mg-rich amorphous silicates determines the formation of hydroxyl groups. The resulting IR spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The observations by Rosetta/VIRTIS revealed the presence of a 2.9-3.6 𝜇m absorption feature (Capaccioni et al 2015), attributed to a mixture of C-H stretching vibrations in aliphatic and aromatic hydrocarbons, OH-groups in carboxylic acids, N-H groups in ammonium ion (NH + 4 ) salts, and hydroxylated amorphous silicates (Capaccioni et al 2015;Quirico et al 2016;Mennella et al 2020;Poch et al 2020;Raponi et al 2020). Filacchione et al (2016) found that the band depth varies slightly across the nucleus and defined three classes: #1) shallow band depth (< 10 per cent) common in Aker, Anubis, Atum, Bastet, Hatmehit, Maftet, and Nut; #2) medium band depth (10-12 per cent) common in Anuket, Apis, Ash, Aten, Imhotep, Khepry, and Ma'at; #3) deeper band depth (> 12 per cent) common in Babi, Hapi, Hathor, and Seth.…”
Section: Discussionmentioning
confidence: 99%
“…The observations by Rosetta/VIRTIS revealed the presence of a 2.9-3.6 𝜇m absorption feature (Capaccioni et al 2015), attributed to a mixture of C-H stretching vibrations in aliphatic and aromatic hydrocarbons, OH-groups in carboxylic acids, N-H groups in ammonium ion (NH + 4 ) salts, and hydroxylated amorphous silicates (Capaccioni et al 2015;Quirico et al 2016;Mennella et al 2020;Poch et al 2020;Raponi et al 2020). Filacchione et al (2016) found that the band depth varies slightly across the nucleus and defined three classes: #1) shallow band depth (< 10 per cent) common in Aker, Anubis, Atum, Bastet, Hatmehit, Maftet, and Nut; #2) medium band depth (10-12 per cent) common in Anuket, Apis, Ash, Aten, Imhotep, Khepry, and Ma'at; #3) deeper band depth (> 12 per cent) common in Babi, Hapi, Hathor, and Seth.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperspectral images (0.25-5 µm) of the nucleus acquired by VIRTIS during the pre-perihelion phase, when the comet was orbiting at heliocentric distance of 3.6-3.3 AU (Capaccioni et al 2015;Filacchione et al 2016a) are characterized by a red slope on I/F visible and infrared spectra and display a broad absorption feature between 2.9 µm and 3.6 µm (referred to as 3.2 µm absorption) superimposed over the thermal emission which extends down to approximately 3 µm (Figure 4). The 3.2 µm absorption has been interpreted as carried by a combination of ammoniated salts (Poch et al 2020), organic materials (Capaccioni et al 2015;Quirico et al 2016;Raponi et al 2020), and hydroxylated silicates (Mennella et al 2020), as discussed in greater detail in next Sections 3.2 -3.3. The I/F spectra of most of the surface do not display the diagnostic absorption features of water ice at 1.5 and 2.0 µm, a result which is compatible with the lack of extended ice-rich patches with sizes much larger than few-tens of meter (See section 3.1).…”
Section: Uv-vis-ir Spectral Properties From Optical Remote Sensingmentioning
confidence: 99%
“…The silicate core composition is deduced by comparing astronomical IR observations with spectra from laboratory silicate samples, suggesting that Mg rich-silicates such as pyroxene (Mg 1− n Fe n SiO 3 ) and/or olivine (Mg 2− n Fe n SiO 4 ) in pure state or in mixtures are the main components (Jäger et al, 2003 ; Escatllar et al, 2019 ). Furthermore, the surface of the Mg-silicate core is probably covered by -OH groups (Kerkeni et al, 2017 ) marked by the presence of the 3.2 μm band detected by the Rosetta probe on the nucleus surface of comet 67P/ Churyumov–Gerasimenko (Mennella et al, 2020 ). However, due to the harsh conditions (T, radiation, collisions) and/or various reprocessing phases (Bromley et al, 2014 ), the silicate surface can be covered not only by silanols or charged groups but by siloxyl (SiO•) or silyl (Si•) radicals, too (Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%